2014
DOI: 10.1016/j.beproc.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal maps in appetitive Pavlovian conditioning

Abstract: Previous research suggests animals may integrate temporal information into mental representations, or temporal maps. We examined the parameters under which animals integrate temporal information in three appetitive conditioning experiments. In Experiment 1 the temporal relationship between 2 auditory cues was established during sensory preconditioning (SPC). Subsequently, rats were given first order conditioning (FOC) with one of the cues. Results showed integration of the order of cues between the SPC and FOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This leads to the prediction that second-order conditioning should be comparatively weak given that simultaneous conditioning generally results in weak anticipatory CR's (see above). Indeed, Cole et al [57] confirmed that this is the case [see also 32,54 for related evidence in appetitive conditioning] by comparing standard second-order conditioning with trace second-order conditioning (Figure 1B). Trace conditioning resulted in weaker initial conditioning, and thus should support weaker mediated association transfer to CS2.…”
Section: Time Affects Acquisition Speed and Asymptotementioning
confidence: 76%
See 1 more Smart Citation
“…This leads to the prediction that second-order conditioning should be comparatively weak given that simultaneous conditioning generally results in weak anticipatory CR's (see above). Indeed, Cole et al [57] confirmed that this is the case [see also 32,54 for related evidence in appetitive conditioning] by comparing standard second-order conditioning with trace second-order conditioning (Figure 1B). Trace conditioning resulted in weaker initial conditioning, and thus should support weaker mediated association transfer to CS2.…”
Section: Time Affects Acquisition Speed and Asymptotementioning
confidence: 76%
“…A related piece of evidence that times are encoded comes from demonstrations that animals can integrate information about time across separate experiences [52-54]. In second-order conditioning, a CS1 is followed by the US, and then CS1 is later paired with a novel CS2 in the absence of the US (Figure 1A).…”
Section: Time Affects Acquisition Speed and Asymptotementioning
confidence: 99%
“…A review of the animal literature suggests that there may be ontogenetic differences in the parameters that support the formation of an association during phase 1 of SPC. In studies of SPC with adult organisms, S 1 and S 2 are typically preexposed sequentially (e.g., Brogden, ; Taylor, Joseph, Zhao, & Balsam, ). Although mature organisms exhibit evidence of SPC following simultaneous preexposure (Matzel, Held, & Miller, ; Rescorla, ), the magnitude of SPC is often greater with sequential preexposure (Hoffeld, Thompson, & Brogden, ; Silver & Meyer, ; Wynne & Brogden, ).…”
Section: Sensory Preconditioning (Spc)mentioning
confidence: 99%
“…Various permutations of this basic design have extended this effect (Molet & Miller 2014), which we cannot detail for brevity. However, these experiments strongly suggest that animals not only order the shuffled fragments of an implied sequence, they also represent the continuous intervals that separate each event it contains (Molet et al 2012;Taylor et al 2014). In other words, animals represent the temporal locations of items within a continuous temporal map, much like they track the spatial locations of items within a spatial map.…”
Section: Introductionmentioning
confidence: 99%